Answer:
(a) x = 3, one solution
(b) x = -10, one solution
(c) infinite solutions
Step-by-step explanation:
In each case, we can subtract the right side from both sides and simplify.
(a)
(2x +4(x -1)) -(2 +4x) = 0
2x +4x -4 -2 -4x = 0 . . . . . . eliminate parentheses
2x -6 = 0 . . . . . . . . . . . . . . . collect terms
x - 3 = 0 . . . . . . . . . . . . . . . . divide by 2
x = 3 . . . . . . . . . . . . . . . . . . . add 3, one solution
__
(b)
25 -x -(15 -(3x +10)) = 0
25 -x -15 +3x +10 = 0 . . . . . . eliminate parentheses
2x +20 = 0 . . . . . . . . . . . . . . .collect terms
x +10 = 0 . . . . . . . . . . . . . . . . divide by 2
x = -10 . . . . . . . . . . . . . . . . . . add -10, one solution
__
(c)
4x - (2x+2x+5(x-x)) = 0
4x -2x -2x +0 = 0
0 = 0 . . . . . . . . . . . . . . . . . . . true for all values of x, infinite solutions